Outside directors and firm performance during institutional transitions - Peng, Mike W. (Strategic Management Journal, 2004)
Abstract Do outside directors on corporate boards make a difference in firm performance during institutional transitions? What leads to the practice of appointing outside directors in the absence of legal mandate? This article addresses these two important questions by drawing not only on agency theory, but also resource dependence and institutional theories. Taking advantage of China's institutional transitions, our findings, based on an archival database covering 405 publicly listed firms and 1211 company–years, suggest that outsider directors do make a difference in firm performance, if such performance is measured by sales growth, and that they have little impact on financial performance such as return on equity (ROE). The results also document a bandwagon effect behind the diffusion of the practice of appointing outsiders to corporate boards. The article not only highlights the need to incorporate multiple theories beyond agency theory in corporate governance research, but also generates policy implications in light of the recent trend toward having more outside directors on corporate boards in emerging economies. Copyright © 2004 John Wiley & Sons, Ltd.